111 Rates and Risk Factors for Hospital Admission in People With Dementia: Systematic Review. (6th February 2020) - Shepherd, H; Livingston, G; Chan, J; Sommerlad, A
Abstract: Background: Hospitalisation is often harmful for people with dementia and results in high societal costs, so avoidance of unnecessary admissions is a global priority. However, no intervention has yet reduced admissions of community-dwelling people with dementia. We therefore aimed to examine hospitalisation rates of people with dementia and whether these differ from people without dementia, and to identify socio-demographic and clinical predictors of hospitalisation. Methods: We searched MEDLINE, Embase and PsycINFO from inception to May 9, 2019. We included observational studies which (1) examined community-dwelling people with dementia of any age or dementia subtype, (2) diagnosed dementia using validated diagnostic criteria, and (3) examined all-cause general (i.e. non-psychiatric) hospital admissions. Two authors screened abstracts for inclusion and independently extracted data and assessed included studies for risk of bias. Three authors graded evidence strength using Cochrane's GRADE approach, including assessing for evidence of publication bias using Begg's test. We used random effects meta-analysis to pool estimates for hospitalisation risk in people with and without dementia. Results: We included 34 studies of 277, 432 people with dementia; 17 from US, 15 from Europe and 2 from Asia. Pooled relative risk of hospitalisation for people with dementia compared to those without was 1.42 (95% confidence interval 1.21, 1.66) in studies adjusted for age, sex, and physical comorbidity. Hospitalisation rates in people with dementia was between 0.37 and 1.26/person-year in high-quality studies. There was strong evidence that admission is associated with older age, and moderately strong evidence that multimorbidity, polypharmacy, and lower functional ability are associated with admission. There was strong evidence that dementia severity alone is not associated. Conclusions: People with dementia are more frequently admitted to hospital than those without dementia, independent of physical comorbidities. Future interventions to reduce unnecessary hospitalisations should target potentially-modifiable factors, such as polypharmacy and functional ability, in high-risk populations.